2002
DOI: 10.1016/s0735-1097(02)02171-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher myocardial strain rates duringisovolumic relaxation phase than duringejection characterize acutely ischemic myocardium

Abstract: In the presence of reduced regional systolic deformation, a higher rate of PSS than systolic shortening identifies acutely ischemic myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…This (passive) mechanism was also suggested by Skulstad et al 28 To be able to discriminate ischemic PST from other forms, it was suggested that changes in strain rate during isovolumic relaxation could be used. 67,68 It was Figure 9. A, The influence of the amplitude of the contractile force on the deformation pattern.…”
Section: Postsystolic Thickening: What Is It and Why Does It Occur?mentioning
confidence: 99%
See 1 more Smart Citation
“…This (passive) mechanism was also suggested by Skulstad et al 28 To be able to discriminate ischemic PST from other forms, it was suggested that changes in strain rate during isovolumic relaxation could be used. 67,68 It was Figure 9. A, The influence of the amplitude of the contractile force on the deformation pattern.…”
Section: Postsystolic Thickening: What Is It and Why Does It Occur?mentioning
confidence: 99%
“…suggested that, in ischemia, the ratio between maximal strain rate during isovolumic relaxation and systole is larger than unity 67 and that, in the radial direction, maximal strain-rate during isovolumic relaxation is positive in ischemia but negative in other forms of PST. 68 In summary, PST will be present in all cases where an imbalance exists at the moment left ventricular pressure drops (aortic valve closure), between deformation of neighboring segments, regardless whether this imbalance is caused by reduced contractility as a result of ischemia, high regional wall stress in some segments (mainly basal septum and in the presence of increased afterload), or regionally delayed contraction.…”
Section: Postsystolic Thickening: What Is It and Why Does It Occur?mentioning
confidence: 99%
“…Fourth, we did not investigate the relationship between the selected parameters and the degree of stenosis of the coronary artery. Fifth, PSS is not specific for ischemia because it can occur in hypertensive heart disease, hypertrophic cardiomyopathy, dilated cardiomyopathy, left bundle branch block, and normal hearts (20,29,30). Sixth, this study excluded patients with prior myocardial infarction because the QGS method has limited ability to evaluate LV thickening in areas of low perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to compare local measurements to global measurement for analyzing regional wall motion. In this situation, myocardial thickening or shortening, i.e., postsystolic shortening, occurs after aortic valve closure [41]. Timing of aortic and mitral valve closure is important to recognize presence of postsystolic shortening.…”
Section: Strain Rate Imagingmentioning
confidence: 99%